Reproducibility in measuring physical activity in children and adolescents with an acquired brain injury - Baque, E.; Barber, L.; Sakzewski, L.; Boyd, Roslyn (Informa UK Limited, 2016)
© 2016 Taylor & Francis Group, LLC. Aim: To examine the reproducibility in measurement of physical activity performance using the ActiGraph® GT3X+ accelerometer in children aged 8–16 years with Acquired Brain Injury (ABI). Methods: Reproducibility of standardized tasks: Thirty-two children with ABI (12 years 1 month, SD = 2 years 4 months; 20 males; Gross Motor Function Classification System I = 17, II = 15) performed the following activities on 2 consecutive days while wearing an accelerometer and a heart rate monitor: quiet sitting, slow walking (SW), moderate walking (MW), fast walking (FW) and rapid stepping on/off a block (STEP). Intra-class correlation coefficients (ICC) were calculated. Performance variability: Fifty-one participants (12 years 1 month, SD = 2 years 5 months; 27 males; GMFCS I = 26, II = 25) wore an accelerometer for 4 days in the community and reliability coefficients were calculated using standardized 12-hour time spent in moderate-to-vigorous physical activity (MVPA). Results: Test–re-test reproducibility was excellent for all activities (SW, ICC = 0.90; MW, ICC = 0.83; FW, ICC = 0.91; STEP, ICC = 0.89). Three days of monitoring produced excellent variability estimates of MVPA (R = 0.78). Conclusion: Therapists can confidently use accelerometry as a reproducible measure of physical activity under standardized walking and stepping conditions, as well as in the community for children with ABI.